Analisis Hubungan Kebiasaan Masyarakat dan Kondisi Fisik Rumah terhadap Kejadian Malaria di Desa Sukajaya Lempasing, Kabupaten Pesawaran Tahun 2025 - Syukma Dewi Octavie Y.; Betta Kurniawan; Nanda Fitri Wardani; Jhons Fatriyadi Suwandi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Malaria remains a significant global health challenge, with Indonesia ranking second in Asia for the highest number of cases. This study aims to analyze the relationship between community habits and physical house conditions with the incidence of malaria in Sukajaya Lempasing Village, Pesawaran Regency. A quantitative method with a case-control design was employed, involving 128 respondents (64 cases and 64 controls) selected through simple random sampling and neighborhood control. Data were collected via interviews and direct observations using structured questionnaires. Bivariate analysis using the Chi-Square test revealed a significant relationship between non-protective habits and malaria incidence (p-value 0.045, OR 2.255), as well as between risky physical house conditions and malaria (p-value 0.043, OR 2.524). Individuals with poor prevention habits and those living in houses without proper ceilings or wire mesh face a higher risk. These findings imply that malaria control in the area requires integrated interventions focusing on individual behavioral changes such as using repellent and long-sleeved clothing alongside physical housing improvements like installing home ventilation screens.